The influence of leadership, work environment and work discipline on employee performance at the central statistical agency of north labuhanbatu district - Muhammad Yuda Hatta; Teguh Setiawan; Sunaryo Sunaryo (Jurnal Scientia, 2024)
This research aims to determine the influence of leadership, work environment and work discipline on employee performance at the North Labuhanbatu Regency Central Statistics Agency (BPS) office. The path analysis research design is used as an analytical tool to determine the direction of the variables being studied and to justify how significant the influence of the independent variable is on the dependent variable, both directly and indirectly. This research uses a descriptive analytical method with a cross sectional approach. In this study, the entire sample population was 113 employees who worked at the North Labuhanbatu Regency Central Statistics Agency (BPS) Office. The research results show that the Leadership variable has no significant effect on employee performance, the work environment has a significant effect on employee performance, work discipline has a significant effect on employee performance. Leadership, work environment and work discipline have a significant effect on employee performance.